Cenários prospectivos da produção do biodiesel no Brasil em 2020 - Sousa, Camille Simeoni Gomes de (2013)
The biodiesel market in Brazil is going through a period of great transformation. Currently, we see a large sector effort to establish itself in the market, but this is still very dependent on the participation of the Federal Government to enter Rules and Regulations that dictate the guidelines of the market as a whole. We know that biofuels stand out as enablers of great opportunities to many countries and social groups, especially those related to agricultural production, and biodiesel is one of the most popular biofuels, this can replace partially or fully the fossil fuels, providing a reduction in expenses related to importation of petroleum and diesel. Biodiesel can also assist in reducing GHGs and increase the generation of employment and income throughout its supply chain. This research aims to develop future scenarios for biodiesel in Brazil in 2020, considering the major social, political, economic and regulatory variables analyzed were raised through a personal survey with industry experts. For this analysis, we used the method of preparation of scenarios described by Grumbach, with the support of software Puma. This methodology provides an analysis of the current situation (supply, demand, regulation), identifying the key variables of the sector (carriers of future events), investigating the interaction between these variables (Method Cross Impact) and, finally, the preparation and interpretation of future scenarios of the biodiesel industry in the set period of time, trying to prepare the system for possible changes in the form of interaction events.